IMPLICATIONS OF BRUNER'S COGNITIVE THEORY ON ELEMENTARY SCHOOL EDUCATION IN THE 21ST CENTURY - Nur Arsyad, Susalti; Tangkin, Wiyun Philipus; Sumartono, Sumartono; Astuti, Budi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Jerome Bruner's cognitive theory plays a significant role in modern education, particularly in primary education, by emphasizing active student involvement in the learning process. This theory is structured around three stages of learning: enactive, iconic, and symbolic. Bruner's discovery learning approach encourages students to construct knowledge through exploration, fostering critical thinking, creativity, and problem-solving. The spiral curriculum further supports continuous learning, revisiting basic concepts at progressively complex levels. In the context of 21st-century education, Bruner's theory aligns well with the development of higher-order thinking skills, communication, and collaboration, supported by the integration of technology. Despite the promising outcomes, challenges such as limited resources, teacher training, and technology integration remain. This literature review explores studies from 2010 to 2024 that analyze the application of Bruner's cognitive theory in primary education, with a focus on the effectiveness of discovery learning, scaffolding, and spiral curriculum in fostering critical thinking and 21st-century skills